Postconcussion discharge advice does not improve concussion knowledge in a community sample. Issue 6 (14th June 2022) - Sullivan, Karen; Kinmond, Sally; Singaravelu Jaganathan, Kannan
Abstract : Objective: Poor concussion knowledge in the community has been linked to reduced injury identification. This study investigated if concussion knowledge could be improved by providing standard postinjury advice (written brochure). Methods: This study was a prospective, controlled study, with random allocation of 199 Australian adults to receive either a concussion information (CI, n=101), or non-CI (n=98). All participants completed the Rosenbaum Concussion Knowledge and Attitudes Survey on three occasions: pre-education and posteducation, and 1 week later. Results: A 2 (condition) × 3 (occasion) mixed analysis of variance with concussion knowledge as the dependent variable did not find a statistically significant interaction (p>0.05). This result was unchanged: (1) with the covariate addition of background education and; (2) in a subgroup analysis (individuals with initially 'low' self-rated knowledge). Some key misconceptions about concussion were identified. Conclusion: The community knowledge of concussion was not significantly improved by the concussion advice. Since injury recognition relies ton an extent on community knowledge, the identified misconceptions should be addressed. This could occur via public health messaging. In clinical settings and for future research, the next steps should also include regular updating of concussion information to keep pace with advances in the field.